Soliton solutions of nonlinear wave equation in finite de-formation elastic cylindrical rod by solitary wave ansatz method - Subhaschandra Singh, Salam (International Journal of Physical Research, 2016)
In this paper, we consider nonlinear wave equation in finite deformation elastic cylindrical rod and obtain soliton solutions by Solitary Wave Ansatz method. It is shown that the ansatz method provides a very effective and powerful mathematical tool for obtaining solutions for Nonlinear Evolution Equations (NLEEs) in nonlinear Science.Elastic Rod; Finite Deformation; Nonlinear Wave Equation; Solitary Wave Ansatz Method; Soliton.